GREEN HRM AND ESG PERFORMANCE: THE MODERATING ROLE OF TRANSFORMATIONAL LEADERSHIP - Teguh, Leonardus; Jaenudin, Dendin (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Sustainability issues and Environmental, Social, and Governance (ESG) performance are increasingly becoming strategic priorities for global companies, yet a significant gap remains between formal Green Human Resource Management (Green HRM) policies and their implementation at the employee level. Data shows that most companies are not yet ready for ESG assessments, while only a small percentage of employees believe their organizations are making sufficient contributions to climate issues. This study aims to explore the role of transformational leadership in bridging this gap to strengthen the impact of Green HRM on ESG performance. Using a narrative review approach, relevant literature from Scopus and Web of Science was critically analyzed. The study revealed that transformational leadership, through inspiration, intellectual stimulation, and individual attention, can encourage employee green behavior, reduce resistance, and foster a sustainability-oriented culture. Thus, transformational leadership plays an essential linking mechanism in ensuring the effectiveness of Green HRM policies in improving ESG performance.